ANALISIS KEPUASAN WISATAWAN TENTANG PENERAPAN SAPTA PESONA DI OBJEK WISATA PANTAI AIR MANIS PADANG - Syahputra, Robby; Silfeni, Silfeni; Abrian, Youmil (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
The study aims to analyze and to know the level of satisfaction of tourist about the application of the armed forces a tourist attraction in Pantai Air Manis Padang. Type of this research is descriptive quantitative data using survey method. Population in this research amounted 1.173 people. Sampling method is non probability sampling, using purposive sampling. Sample number in this research amounted to 93 people. Data collection using a questionnaire using likert scale that tested for validity and reliability. Furthermore data analyzed by descriptive analysis with importance performance analisysis (IPA). The result of this research is that it is cocluded that in general analysis of sapta enchantment in Pantai Air Manis Padang from 93 of respondents declared that 44,68% of very satisfied, 34,04% less satisfied and 21,28% are not satisfied.Key words: Analysis, Armed Forces Enchanment, Tourists